An impurity intermediate band due to Pb doping induced promising thermoelectric performance of Ca5In2Sb6. Issue 23 (21st June 2015) - Feng, Zhenzhen; Wang, Yuanxu; Yan, Yuli; Zhang, Guangbiao; Yang, Jueming; Zhang, Jihua; Wang, Chao
<x xml:space="preserve">Abstract</x> Pb doping introduces a partially filled intermediate band in the band gap of Ca5In2Sb6, which will increase the electrical conductivity and has little detrimental effect on its Seebeck coefficient.